Effect of crotonylidene diurea on soil enzyme activity and nutrient availability in a Vertisol - Pawar, Atul Bhagawan; Chauhan, M R; Kale, K D; Chobhe, Kapil Atmaram; Verma, Anil Kumar; Trivedi, Vivek Kumar; Louhar, Ganpa t; Rekwar, Rav indra Kumar (The Indian Journal of Agricultural Sciences, 2020)
The release of nitrogen (N) from slow release N fertilizers (SRNF) is affected by soil microbial activity. However, several studies have shown variable results regarding the effect of microbial population size on the release of nutrient from slow release fertilizers. To understand this relationship clearly, changes in activities of two soil enzymes (urease and dehydrogenase), microbial population and available macronutrients viz nitrogen (N), phosphorus (P) and potassium (K) were assessed in an incubation study conducted under ambient condition. The six treatments were used for present investigation as control, 100% urea and crotonylidene diurea (CDU) @ 100, 75, 50 and 25% of recommended dose. The results indicated that the addition of N through commercially available urea and CDU as per general recommended dose of nutrients (GRDN) showed an increase in soil enzyme activity, microbial population, available N, P and K. The urease enzyme activity was found to be highest of nutrients in GRDN treatment at 60 days after addition (DAA) (39.55 μg NH4+-N/g soil/hr) and in 100% N through CDU (37.45 μg NH4+-N/g soil/hr) at 90 DAA. The soil dehydrogenase enzyme activity was significantly higher in GRDN at 7, 14, 21 and 30 DAA (1.32, 1.44, 1.56 and 1.68 μg TPF/g soil/hr, respectively). However, at 60 and 90 DAA the dehydrogenase enzyme activity was significantly higher in 100% N through CDU (1.89 and 1.63 μg TPF/g soil/hr, respectively). The soil available N content increased up to 60 DAA in all the treatments and it was significantly higher in GRDN followed by 100% N through CDU. However, it was significantly higher at all the periods of incubation over 75, 50, 25 and 100% N through CDU.